The Late Eighteenth Century - Strunk, Oliver 1901-1980; Allanbrook, Wye Jamison 1943-2010 (New York Norton, 1997)
The era of Haydn, Mozart, and early Beethoven not only produced music of enduring appeal, it also gave us significant writings that explain how music should be composed, performed, listened to, and understood. Included are selections from the great German pedagogical treaties of Quantz (on playing the flute), C. P. E. Bach (keyboard), Leopold Mozart (violin), and Kirnberger and Koch (on composition); opinions about opera by Rousseau, Diderot, and Gluck; ideas on expression by W. A. Mozart and G. de Staël; and historical/descriptive writings of Forkel, Charles Burney, and Susannah Burney.
Keywords: 18th Century (1701-1800); Music philosophy and esthetics; Music theory; Music history